THE INFLUENCE OF INDEPENDENCE, PROFESSIONALISM, AND ORGANIZATIONAL COMMITMENT TO PERFORMANCE AUDITORS IN PUBLIC ACCOUNTANT OFFICE IN MEDAN CITY - Fachruddin, Wan (Lembaga Jurnal & Seminar Universitas Pembangunan Panca Budi, 2019)
This study aims to examine and analyze the effect of independence on auditor performance, the effect of professionalism on auditor performance and the effect of organizational commitment on auditor performance. In this study the authors used an associative approach, the source of the data used was primary data. Data collection techniques used are by distributing questionnaires/questionnaires to 47 auditors who work at the Public Accountant Office in the City of Medan. The sampling technique used in this study is saturated sampling. Data analysis techniques used in this study were descriptive statistical tests, multiple regression analysis, classic assumption tests, hypothesis testing and coefficient of determination tests. The results of this study indicate that 1) Independence has no effect on Auditor Performance, 2) Professionalism has a significant effect on Auditor Performance, 3) Organizational Commitment has a significant effect on Auditor Performance. 4) Independence, Professionalism and Organizational Commitment simultaneously influence the Auditor's Performance.